Relações treonina : lisina digestíveis e níveis de energia líquida para suínos - Paiano, Diovani (2007)
Five studies were carried out to evaluate the effect of digestible threonine:lysine ratios (TL) for starting, growing and finishing pigs and the effect of net energy levels. The Studies I and II was evaluated the effect of TL on the use of the nitrogen (N) of starting and growing pigs. Was carried out two studies with barrows of high-lean commercial crossbred. The Experiments I and III, was a nitrogen balance, using 20 barrows with the initial weight 23.0±4.1 kg and 15 pigs with initial weight 37.0±2.6 kg, respectively, for studies I and III. The pigs were allotted in a randomized design, with five TL ratios. Diets had low crude protein levels (17.3 % and 14.7%) and the TL ratio: 0.574; 0.624; 0.673; 0.722 and 0.772 were used. In the Experiment I, the excreted crude protein (CPE), crude protein retention (CPR), net protein utilization (NPU), showed quadratic effect. The best TL ratio was 0.649 (average of the CPR and NPU). In the Exp. III, the crude protein absorbed (CPAB) and the plasma urea nitrogen (PUN) had quadratic effect and the best TL ratio value was 0.658 (average of CPAB and PUN). The Exp. II, was conducted to examine the effects of same TL ratio on performance of starting pigs, 60 pigs (30 barrows and 30 gilts), with the initial weight of 15.5±1.5 kg, from the same farm of Exp. I. The pigs were allotted in a randomized design, following a factorial scheme, with two sexes and five TL ratios. Were used six pens for treatments (3 barrows and 3 gilts). The treatments were the same of the Experiment I. In the Experiment II no had effect of TL ratio on daily feed intake (DFI) and average weigh gain (AWG). However the feed:gain ratio showed quadratic effect and the best TL was achieved at TL ratio 0.691. The Experiment IV was conducted to evaluate the effects of different levels of net energy (NE) for growing and finishing pigs with the best TL obtained in Experiment II. Forty pigs with initial weight 30.2±1.3 kg (20 barrows and 20 gilts), from the same farm of Experiment I, were allotted in a randomized design, xiv following a factorial scheme, with two sexes and five net energy levels. Five levels of net energy were used (2,410; 2,450; 2,490; 2,530 and 2,570 kcal/kg), for the growing and finishing diets. In the Experiment IV, daily feed intake (ADFI) decreasing and feed:gain ratio (FGR) improved with the increasing levels of NE in finishing and total period. The backfat thickness deposition increased with the increase level of energy. The Exp. V, was conducted to examine the effects of same TL ratios on performance, carcass traits and meat quality of growing and finishing pigs. Forty pigs (20 barrows and 20 gilts), with initial weight of 30.1±1.8 kg, from the same farm of the Exp. IV were used. The experimental design was the same of exp IV. A corn-soybean meal diet was formulated according to ideal protein concept, with 2,513 kcal NE/kg; 14.7% CP; 0.81% digestible lysine; 0.55% Ca and 0.39% P available for growing and 2,568 kcal DE/kg; 12.5% CP; 0.68% digestible lysine; 0.49% Ca and 0.33% phosphorus available for finishing pigs. Additional synthetic amino acids were supplied as necessary to achieve the TL ratio in the study. In the Experiment V, the FG on growing pigs showed quadratic effect and the best TL ratio value was 0.674. Had no effect of TL ratio on others growth performance characteristics. The abdominal fat of barrows showed quadratic effect and the best TL ratio value was 0.630. The slaughter weight and dry lost had increased linearly. The backfat thickness decreased in growing phase with the increase of the TL ratio. The results suggest that TL ratio 0.649 maximize the nitrogen retention and TL ratio 0.691 optimize the FGR in starting pigs (15-30 kg). The TL ratio 0.658 maximize the nitrogen retention and TL ratio 0,674 optimize the FGR in growing pigs (30-60 kg). The TL ratio 0.630 minimize the abdominal fat in barrows. The rise of TL ratio decreased the backfat thickness in growing pigs and increase the slaughter weight. The increased of the net energy levels decreased the ADFI, optimize FGR and. the backfat thickness deposition increased.